(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses how dreams, as a poetic tool, serve to penetrate the psychological depth of works of art, to effectively reveal the essence of characters and themes. They bring out the dramatic tension in the work and strengthen psychologism. It creates interconnections between plot components and serves to form the composition of the work.